Exposure of volatile organic compounds (VOCS) and neurobehavioural effects among chemical plant workers - Yaakob, Norfarhana (Universiti Sains Malaysia, 2015)
VOCs are carbon-based organic chemicals. VOCs effects human health such as throat irritation, headaches, loss of coordination, nausea, damage to liver, kidney, and central nervous system. A study on exposure of volatile organic compounds (VOCs) and neurobehavioural effects among chemical plant workers has been implemented through comparative cross sectional study. Environmental monitoring of volatile organic compounds (VOCs) was measured using Phocheck+ instruments for three locations which are Process Building, Butadiene Storage and Bioplant (waste area) for 15 minutes three times daily for five days. Neurobehavioural effects were examined among the exposed group of 40 subjects consists of Nitrile Butadiene Rubber (NBR) plant. It was compared with non-exposed of 40 administrative staff. Subjects were asked about socio demographic, work characteristics, health status and neurobehavioural symptoms using a modified questionnaire. Neurobehavioural core test battery tests (NCTB) were conducted for 50 minutes among them. Process building had the highest VOCs concentration in NBR plant compared to Butadiene Storage and Bioplant (waste area). The top three chemicals exposed to workers were butadiene, ammonia and acrynotrile. Only itchiness showed significant association between exposed and non-exposed group (p=0.001). NCTB score showed significant difference between exposed and non-exposed group in Digit Span Forward, Digit Span Backward (auditory memory) and Steadiness Test (hand steadiness and tremor). Only gender in socio demographic factors affecting auditory memory (Digit Span Forward and Digit Span Backward). Smoking affecting visual perception/memory (Benton Visual Retention) and hand steadiness/tremor (Steadiness Test). Health status factors affecting manual dexterity (Minnesota Manual Dexterity (non-dominant). None of the NCTB scores were affected by VOCs exposure or work characteristics. As conclusion, employers must be aware of the chemical exposure which can affect the neurobehavioural of workers in the workplace.